The Role of Great Britain in Forming of EU’s Foreign and Security Policy in the Context of Leading Theories of Eurointegration - A. V. Groubinko (Vestnik MGIMO-Universiteta)
In the article on the basis of the original chart of the theoretical conceptual system of Eurointegration's development offered by an author base principles of Great Britain's participation in common foreign and security policy (CFSP) of the European Union are examined. The country’s role in the processes of forming EU's CFSP is determined in the context of leading theories of Eurointegration. The evolution of British government's policy participation in the system of political co-operation in the European Union, character of its influence on the processes of Eurointegration in the sphere of foreign and security policies are analysed. CFSP as a specific sphere of co-operation of the EU's states fully represents conceptual dichotomy of European Union essence at level «intergovernmental - supranational». CFSP is the segment of the EU's legal reality which is historically based on intergovernmental co-operation, and in modern terms characterized by the expressed elements of funcional supranational institucialisation and insignificant strengthening of federalism. Great Britain conceptual approaches to forming EU's CFSP lie traditions of pragmatical and functional realistic approach with the elements of federalist co-operation, externalism and minimum of institucialism. For activity of British governments is inherent pistorical heredity of participating in political integration within the framework of Common Europe. It's mean a successive policy of inhibition federalist supranational tendencies, propagandas of the evolutional going to development of integration processes and it distribution on new spheres. Such approaches are correspond to the model of selective-sectoral integration or «Europe a la carte» ofThatcherist standards, which in the process of realization under influence of objective (mainly external) factors evolved to practical embodiment of such more soft models of flexible integration, as «multi-speed integration» and «Europe of variable geometries». The noted approaches to CFSP allow government on the different historical stages to have retentive or stimulant influence on the integrational processes.